2021
DOI: 10.1177/03611981211037246
|View full text |Cite
|
Sign up to set email alerts
|

Equity Implications of Ride-Hail Travel during COVID-19 in California

Abstract: COVID-19 has shocked every system in the U.S., including transportation. In the first months of the pandemic, driving and transit use fell far below normal levels. Yet people still need to travel for essential purposes like medical appointments, buying groceries, and—for those who cannot work from home—to work. For some, the pandemic may exacerbate extant travel challenges as transit agencies reduce service hours and frequency. As travelers reevaluate modal options, it remains unclear how one mode—ride-hailing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The study revealed that the pandemic has less severe impact on BSS than subway with less ridership drop and an increase in trips' average duration [16]. Brown & Williams (2023) studied how the patterns of ride-hail trips before COVID-19 pandemic compare with the trips during the pandemic by analyzing aggregated Uber trip data in California [17]. The results showed a significant decrease in ride-hail trips across different regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study revealed that the pandemic has less severe impact on BSS than subway with less ridership drop and an increase in trips' average duration [16]. Brown & Williams (2023) studied how the patterns of ride-hail trips before COVID-19 pandemic compare with the trips during the pandemic by analyzing aggregated Uber trip data in California [17]. The results showed a significant decrease in ride-hail trips across different regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interestingly, the cross elasticity for exclusive ride-sourcing in relation to transit out-of-vehicle travel time is greater for group I1 than for groups I2 and I3. This could be a reflection of the growth in the generation of ride-sourcing trips in lower-income areas that was observed pre-pandemic, or it could be the result of the complementary role that ride-sourcing can play in areas with lower transit accessibility ( 70 ). The results highlight the potential for transportation demand management strategies to have varied impacts across income groups.…”
Section: Elasticity Analysismentioning
confidence: 99%
“…Transit agencies are grappling with the implications of substantial drops in ridership and associated fare revenue, and are being forced into changing service levels (e.g., frequency) and service coverage (both spatially and temporally). These reductions in service levels are further exacerbating the situation as people find it impractical to use transit to meet their mobility needs and increasingly choose to use mobility-as-a-service or other modes to travel ( 11 , 12 ). Transit in the United States was already experiencing a slow decline in ridership in the pre-pandemic era because of a healthy economy (that facilitated high levels of car ownership), affordable fuel prices, and widespread availability of mobility-on-demand services that offered very flexible and convenient transportation.…”
mentioning
confidence: 99%